Struktur Populasi Mangga Kweni (Mangifera odorata Griff) Di Bantaran Sungai Barito Desa Sungai Gampa Kabupaten Barito Kuala - Adawiyah, Rabiatul; Dharmono, Dharmono (Biospecies, 2025)
Population structure is one of the references that can be used to determine the status and existence of a population in a habitat. Kweni mango (Mangifera odorata Griff) is one of the endemic mango species of South Kalimantan. This study aims to examine the population structure of kweni mango (Mangifera odorata Griff) on the banks of the Barito River, SungaiGampa Village, Barito Kuala Regency. The research method applied is total exploration. The results of the study showed that the population structure of kweni mango in the Barito Kula Riverbank area, Sungai Gampa Village has a pyramid shape of a disturbed pitcher with three growth phases, namely pre-reproductive (118.42 ind / km2), reproductive (625 ind / km2), and post-reproductive (111.84 ind / km2). So that kweni mango plants can be categorized as being in a safe or fairly developed condition because they have more than 25 adult individuals in 1 km2.